DAIR for periprosthetic joint infections—One week to save the joint? - Vatsal Gupta; Shafiq Shahban; Michael Petrie; Peter K. Kimani; Jakub Kozdryk; Bryan Riemer; Richard King; Richard Westerman; Pedro Foguet (Arthroplasty, 2024)
Abstract Background Predicting the success of a Debridement, Antibiotics, and Implant Retention (DAIR) procedure for periprosthetic joint infection (PJI) for hip and knee joint arthroplasty remains a challenge. A failed DAIR might adversely affect the outcome of any future revision surgery for PJI. Hence, the ability to identify and optimize factors predictive of DAIR success would help target the procedure to the appropriate patient cohort and avoid unnecessary surgery for patients where a DAIR is unlikely to eradicate infection. Methods A retrospective review of our prospective Bone Infection Group database was performed to identify all patients who underwent a DAIR of their primary or revision hip or knee arthroplasty. All patients had a confirmed PJI as per MSIS 2013 criteria and an outcome according to the MSIS working group outcome-reporting tool. DAIR surgery was then grouped into groups of “successful” or “unsuccessful” outcomes. Results Sixty-four consecutive patients with an acute PJI underwent a DAIR procedure between 2009 and 2020, with 46 procedures performed for knees and 18 for hips. Treatment was successful in 69% (37 knees and 7 hips). The chance of a successful DAIR was significantly greater if performed at or within one week of symptom onset compared to greater than one-week duration (adjusted odds ratio (OR) 0.11; P = 0.027; 95% CI [0.02–0.78])). For DAIR performed at or within one week of symptom onset, the success rate was 93% for knees and 80% for hips. The chance of a successful DAIR however was not influenced by whether the surgeon was an arthroplasty or non-arthroplasty surgeon (OR 0.28; P = 0.13; 95% CI [0.05–1.48])). Isolated Streptococcus infection had a success rate of 100%. Next came Coagulase-negative Staphylococci (71%) and Methicillin-susceptible Staphylococcus Aureus (65%). Polymicrobial infection had the worst outcome, with a success rate of 40%. Conclusion In our experience, DAIR surgery performed within one week of symptom onset significantly increased the chance of successful infection eradication. Collaborative work is required to ensure arthroplasty patients can access prompt appropriate surgical decision-making as soon as concerns arise, remove barriers to early assessment and minimise delays to surgery.